2008
DOI: 10.1093/treephys/28.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Climatic control of bud burst in young seedlings of nine provenances of Norway spruce

Abstract: Detailed knowledge of temperature effects on the timing of dormancy development and bud burst will help evaluate the impacts of climate change on forest trees. We tested the effects of temperature applied during short-day treatment, duration of short-day treatment, duration of chilling and light regime applied during forcing on the timing of bud burst in 1- and 2-year-old seedlings of nine provenances of Norway spruce (Picea abies (L.) Karst.). High temperature during dormancy induction, little or no chilling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 40 publications
7
91
4
1
Order By: Relevance
“…Provenances did not group phylogeographically along the east-western major axis of the species range, but ecologically along a latitudinal/altitudinal gradient, similar to findings in P. canariensis (López et al, 2007) or P. contorta (Chuine et al, 2006). There is also a certain parallelism to the effects of epigenetic memory of cold and warm embryo formation described in other conifers, which are interpreted as a mechanism of adaptative phenotypic plasticity that improves the fitness of the same genotype in different environments (Besnard et al, 2008;Kvaalen and Johnsen, 2008;Søgaard et al, 2008). Against this background one might wonder whether, and to what degree, those moderate differences found between the studied stone pine provenances, distinguishable only after major spatial adjustments (that reflect a common, very stable microsite response of each and every genotype), might also be due to an epigenetic acclimatisation (Vendramin et al, 2008).…”
Section: Discussionsupporting
confidence: 55%
“…Provenances did not group phylogeographically along the east-western major axis of the species range, but ecologically along a latitudinal/altitudinal gradient, similar to findings in P. canariensis (López et al, 2007) or P. contorta (Chuine et al, 2006). There is also a certain parallelism to the effects of epigenetic memory of cold and warm embryo formation described in other conifers, which are interpreted as a mechanism of adaptative phenotypic plasticity that improves the fitness of the same genotype in different environments (Besnard et al, 2008;Kvaalen and Johnsen, 2008;Søgaard et al, 2008). Against this background one might wonder whether, and to what degree, those moderate differences found between the studied stone pine provenances, distinguishable only after major spatial adjustments (that reflect a common, very stable microsite response of each and every genotype), might also be due to an epigenetic acclimatisation (Vendramin et al, 2008).…”
Section: Discussionsupporting
confidence: 55%
“…In Norway, Finland and Sweden, provenance trials found the interior provenances to be superior to the coastal (Kurkela 1981;Magnesen 1987;Martinsson and Kollenmark 2001). Since spring frost hardiness and bud burst occurrence are highly correlated (Howe et al 2003;Søgaard et al 2008), the time of bud burst is a useful indicator of a species suitability for a particular location (Hannerz 1999;Howe et al 2003;Anekonda et al 2004;Gould et al 2011). Christophe and Birot (1979) and Edman (1997) were unable to show a correlation between bud burst occurrence and latitude or elevation of Douglas fir provenances.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of bud scale complex might be considered as a "memory" effect. This could explain, at least on part, why the bud burst is delayed in the following spring in cases, where the SD seedlings were exposed also to higher temperature during bud formation (Dormling et al 1968;Heide 1974b;Søgaard et al 2008;Olsen et al 2014;Wallin et al 2017). SD induced changes in the activity of dormancy-related genes has also been reported to determine the timing of dormancy induction, dormancy release and forthcoming bud burst in Norway spruce seedlings (Wallin et al 2017).…”
Section: Discussionmentioning
confidence: 99%